HIDROPONIK SEBAGAI MEDIA PEMBELAJARAN URBAN FARMING PADA SISWA SISWI SEKOLAH DASAR DAN SEKOLAH MENENGAH DI KOTA MALANG - Putu Hadi Setyarini; Sisca Fajriani; Mochammad Roviq; Dwi Hadi Sulistyarini; Diana Aisyah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
AbstractThe aim of the activity is to teach teachers and students at SDI and SMPIT As Salam about urban farming using the hydroponic technology with vegetable plants. The activity was carried out as a support for P5 subjects in SDI and SBDP at SMPIT As Salam with a total of 75 students, 20 school teachers, 5 lecturers, and 3 university students. Lectures, demonstrations, and individual practice are all part of the activity implementation. The first part of courses and discussions on hydroponic cultivation introduces different types of hydroponics, types of tools and materials used, procurement and preparation of tools and materials, creation of seedbeds using rockwool media, varieties of vegetables that can be grown hydroponically, creation and management of nutrient solutions, maintenance and plant maintenance, harvesting hydroponic vegetables, and handling of hydroponic vegetables after harvest. Demonstrations begin with the preparation of planting media for seedlings, followed by the preparation of nutrient solutions, the transition of planting to hydroponic installations, plant care and maintenance, and the procedures of harvesting and post-harvesting. Individual practice by using growth medium to hydroponically cultivate veggies Pakchoy and pagoda mustard greens are two of the veggies cultivated. The outcomes of the program demonstrate that students can undertake urban farming activities at school and improve the aesthetics of the schoolyard by engaging in hydroponic vegetable cultivation activities. AbstrakTujuan kegiatan yaitu memberikan pengetahuan tentang urban farming dengan metode hidroponik menggunakan tanaman sayuran bagi guru dan siswa-siswi SDI dan SMPIT As Salam. Kegiatan dilaksanakan sebagai penunjang mata pelajaran P5 di SDI dan SBDP di SMPIT As Salam dengan jumlah peserta sebanyak 75 siswa, 20 guru sekolah, 5 dosen pengabdi dan 3 mahasiswa. Pelaksanaan kegiatan meliputi ceramah, demonstrasi, dan praktek individu. Ceramah dan diskusi budidaya secara hidroponik mulai dari pengenalan berbagai jenis hidroponik, jenis bahan dan alat yang digunakan, pengadaan dan penyiapan alat dan bahan, persiapan persemaian bibit menggunakan media rockwool, jenis sayuran yang dapat ditanam secara hidroponik, penyiapan dan pengelolaan larutan nutrisi, perawatan dan pemeliharaan tanaman hingga pemanenan sayuran hidroponik dan penanganan pasca panen sayuran hidroponik. Demonstrasi mulai dari cara persiapan media tanam semai bibit, pembuatan pembuatan larutan nutrisi, pindah tanam ke instalasi hidroponik, perawatan dan pemeliharaan tanaman hingga proses panen dan pasca panen. Praktek individu dengan menanam sayuran secara hidroponik di media tanam. Jenis sayur yang ditanam adalah pakchoy dan sawi pagoda. Hasil kegiatan menunjukkan bahwa melalui kegiatan budidaya sayuran secara hidroponik siswa dapat menerapkan kegiatan urban farming di sekolah sekaligus menata keindahan halaman sekolah.